Petrology and geochemistry of intrusive rocks in Some-Ahani and Ferezneh prospect areas, east of Sangan mine, Khaf (Southeast of Mashhad - Nazi Mazhari; Azadeh Malekzadeh Shafaroudi; Majid Ghaderi (پترولوژی, 2017)
The Some-Ahani and Ferezneh prospect areas are two of the eastern anomalies ofKhaf’s Sangan iron mine in Khorasan Razavi province. Biotite monzonite porphyry andbiotite syenogranite Tertiary plutons occurred in the area of study. Due to the severe alteration of biotite monzonite porphyry intrusion, geochemical studies have beenfocused on the biotite syenogranite. It is chemically peraluminous, moderate to highpotassic and magnesian and its tectonic setting is of post orogenic. In both A-typegranites and in differentiated peralkaline I-type granitic rocks: negative Eu anomaly,mild enrichment of LREE, positive, relatively flat HREE pattern, negative anomalies ofBa, Sr, La, Ce, Ti, and large amount of Ga (16- 24 ppm) are the same. On the basis ofmajor oxide values and SiO2 vs. FeOt/MgO ratio, the prospect area samples fall in therange of I-type granites. Variations in the minor and trace elements in all samplesindicate fractional crystallization in separation of plagioclase, alkali feldspar and biotite,generated by fractional crystallization from an I-type granitic magma poor in P. Increasein HFS elements such as Ga and Nb is associated with the differentiation of thesegranites. Comparison of the intrusions studied with Bermani and Sarkhar rocks insoutheast Sangan shows that variations in the major, minor and rare earth elements aresimilar to each other and to those of I-type granites, which can be differentiated by various degrees of partial melting of andesite and dacite protolith or are produced by atwo-stage process of remelting intermediate rocks.